Analisis Perancangan Model Dashboard dalam Monitoring Data Pelanggan ( Studi Kasus : Toko Xyz ): Analysis of Dashboard Model Design in Monitoring Customer Data (Case Study: Xyz Store) - Sri Hartono (YCMM, 2021)
This study aims to create a Customer Data Monitoring Dashboard at the Xyz Store. Customer control at the xyz store was not done well before because there was no system that could help the xyz store to identify active and passive customers, so a real-time system was needed. It aims to make it easier for top management to control active and passive customers in the xyz store quickly and accurately. The data on the system was obtained from the author's interview with the manager of the xyz store which stated that from 2017 to 2020 there were 811 registered customers of the Xyz store, and made this data also the primary data in this study. While the secondary data used by the author is customer data at the xyz store and then implemented into the customer monitoring dashboard system. The system modeling method used in this study is the Unified Modeling Language (UML), namely use case diagrams, activity diagrams, sequence diagrams, class diagrams, while the system development in this study uses the Macro Process method in Object Oriented Analysis Design (OOAD). ) with the Requirements level. , Analysis and Design, Implementation, Testing and Deployment, this system uses the MySQL database system and the PHP programming language. In the xyz store customer monitoring system, which is packaged in a graphical dashboard display, it will look very attractive and easy to control existing customers. Actors in this system are managers and sales.